Manajemen strategi berbasis data di taspen : menuju keberlanjutan keuangan - Nikmah, RA Ulfatun (Maliki Interdisciplinary Journal, 2025)
Data-driven strategic management is key for PT Taspen in achieving financial sustainability amidst demographic challenges, market fluctuations, and technological disruption. This study examines how PT Taspen, as a Civil Servant Pension Fund management institution, can adopt a data-driven strategic management approach to optimize fund management and ensure long-term solvency. By utilizing data analytics, PT Taspen can improve the accuracy of actuarial predictions, investment risk management, and operational efficiency. The balanced scorecard approach is used as a strategic framework to integrate financial, customer, internal process, and organizational learning perspectives. In addition, digital transformation is a key pillar in supporting the implementation of this strategy through the adoption of technologies such as big data and artificial intelligence. This study shows that data-driven strategic management not only improves financial performance but also strengthens PT Taspen's competitiveness in the modern financial ecosystem. Recommendations include strengthening technological capabilities and human resource training to support sustainable financial sustainability.